2013
DOI: 10.1109/lgrs.2012.2209626
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the AIEM Through Correlation Length Parameterization at Field Scale Using Radar Imagery in a Semi-Arid Environment

Abstract: Abstract-This work aimed to validate the Advanced Integral Equation Model (AIEM) through different correlation length parameterizations using radar imagery for field-scale studies in a semi-arid environment. The study compared backscattering coefficients simulated from the AIEM and retrieved from SAR imagery of a study site in Sardinia. Two treatments for correlation length were adopted: in situ measurements and empirically based correlation length estimation. The results showed an overestimation of backscatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Some researchers work at field scale using theoretical inversion models with radar images Brogioni et al, 2010;Dong et al, 2013;Nearing et al, 2010;Wu et al, 2008). Those studies are essential to the understanding of radar signal interaction with soil parameters in order to improve the estimation of surface SM for various ground types.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers work at field scale using theoretical inversion models with radar images Brogioni et al, 2010;Dong et al, 2013;Nearing et al, 2010;Wu et al, 2008). Those studies are essential to the understanding of radar signal interaction with soil parameters in order to improve the estimation of surface SM for various ground types.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed that the use of the calibrated correlation length, as proposed by Baghdadi et al [14][15][16][17][18][19] is able to improves the performance of the IEM at both both HH and VV polarizations [35][36][37]. Dong et al [36] used the calibrated correlation length in the AIEM to simulate SAR data in C-band.…”
Section: Introductionmentioning
confidence: 91%
“…Several studies showed that the use of the fitting parameter Lopt allows more correct estimations of the radar backscattering coefficient [36].…”
Section: Iem Modified By Baghdadi (Iem_b)mentioning
confidence: 99%
See 1 more Smart Citation
“…The model is capable of simulating the scattering by and emissions from the natural land surface for a wide range of dielectric and roughness conditions and remote sensor configurations. The model is highly accurate and has been widely used in microwave scattering and emission analyses and soil moisture retrieval [8], [17], [18]. Compared with the IEM, two improvements have been incorporated into the AIEM: 1) it includes complete expressions for the Kirchhoff field coefficient and complementary field coefficient (see Fig.…”
Section: A Description Of the Aiemmentioning
confidence: 99%